Moa Martinson Visiting Professor - Stylianou-Lambert, Theopisti (My University, 2026)
The Moa Martinson and Tage Danielsson professorships at Linköping University are intended for researchers in the humanities and social sciences, or those active in the arts. The professorship programmes aim to uphold values such as culture, humanism, and social commitment. These are values powerfully embodied by the cherished Swedishauthors and artists Moa Martinson and Tage Danielsson. I got awarded the 2025-2026 Moa Martinson Visiting Professor Award. More information about my award here: https://liu.se/en/news-item/theopisti-stylianou-lambert-utsedd-till-nasta-gastprofessor-i-moa-martinsons-namn
Keywords: Arts and entertainment